Application of the broadband collision‐induced dissociation (bbCID) mass spectrometry approach for protein glycosylation and phosphorylation analysis. (13th December 2017) - Couto, Narciso; Davlyatova, Liliya; Evans, Caroline A.; Wright, Phillip C.
Abstract : Rationale: Analysis of post‐translationally modified peptides by mass spectrometry (MS) remains incomplete, in part due to incomplete sampling of all peptides which is inherent to traditional data‐dependent acquisition (DDA). An alternative MS approach, data‐independent acquisition (DIA), enables comprehensive recording of all detectable precursor and product ions, independent of precursor intensity. The use of broadband collision‐induced dissociation (bbCID), a DIA method, was evaluated for the identification of protein glycosylation and phosphorylation. Methods: bbCID was applied to identify glycopeptides and phosphopeptides generated from standard proteins using a high‐resolution Bruker maXis 3G mass spectrometer. In bbCID, precursor and product ion spectra were obtained by alternating low and high collision energy. Precursor ions were assigned manually based on the detection of diagnostic ions specific to either glycosylation or phosphorylation. The composition of the glycan modification was resolved in the positive ion mode, while the level of phosphorylation was investigated in the negative ion mode. Results: The results demonstrate for the first time that the use of a bbCID approach is suitable for the identification of glycopeptides and phosphopeptides based on the detection of specific diagnostic and associated precursor ions. The novel use of bbCID in negative ion mode allowed the discrimination of singly and multiply phosphorylated peptides based on the detection of phosphate diagnostic ions. The results also demonstrate the ability of this approach to allow the identification of glycan composition in N‐ and O‐linked glycopeptides, in positive ion mode. Conclusions: We contend that bbCID is a valuable addition to the existing toolkit for PTM discovery. Moreover, this technique could be employed to direct targeted proteomics methods, particularly where there is no a priori information on glycosylation or phosphorylation status. This technique is immediately relevant to the characterisation of individual proteins or biological samples of low complexity, as demonstrated for the analysis of the glycosylation status of a therapeutic protein.